The Effect of Discovery Learning Model on Students’ Learning Competencies At Grade VII In Junior High School 16 Padang - Nofianti Nofianti; Helendra Helendra; Yosi Laila Rahmi; Ristiono Ristiono (Universitas Negeri Padang, 2020)
The low level of students’ science learning competencies at grade VII in Junior High School 16 Padang is caused by several factors, one of them is the learning process still used teacher-centered, so the students tend to inactive in the learning process. Therefore, it is necessary to conduct an innovative learning process in order to improve students’ competencies, in knowledge, attitudes and skill. One of the method that can be used by the teacher is by implementing the Discovery Learning model. The aim of this study is to determine the effect of the Discovery Learning model through students’ learning competencies in science (knowledge, attitudes and skill) at grade VII in Junior High School 16 Padang. This type of research is experimental research with a control group posttest only design. The population in this study were all class VII SMPN 16 Padang registered in the 2018/2019. Sampling was done using technique purposive sampling, which was chosen as the sample of the study was class VII.5 as the experimental and VII.2 as the control class. The instruments used were in the form of questions posttest for knowledge competencies, observation sheets for attitide and skills. The hypothesis was tested using the t-test, can be concluded that the competencies of learners knowledge tcount 5,96 > ttable 1,67, the competencies of attitude value tcount 6,36 > ttable 1,67, and the competencies of skills value tcount1,69 > ttable1,67. This shows that the hypothesis is accepted. Concluded that the application of model the Discovery Learning has a positive effect on students’ science learning competency of knowledge, attitudes and skills of class VII students of SMPN 16 Padang.